389 Is the Higher Prevalence of Asthmatic Symptoms following Preterm Birth Restricted to Childhood?. (October 2012) - Damgaard, ALDB; Mathiasen, R; Hansen, BM; Buchvald, F; Greisen, G
Abstract : Background and Aim: Preterm birth is associated with increased risk of asthmatic symptoms in childhood, but it seems uncertain whether this association persists into adulthood. We have investigated the association between gestational age (GA) and the use of prescription asthma medication in young adults. Methods: This is a register study of a Danish national cohort of all infants born 1980–1989 and followed up at the age of 21–30 years. The retrieval of prescription asthma medication (inhaled beta-2 agonists and/or inhaled corticosteroids and/or oral leukotriene antagonists) in 2009–2010 was evaluated. Logistic regression analyses were performed to determine the relationship between the use of asthma medication and gestational age, adjusted for gender, small-for-gestational age and multiple births. Results: Data were obtained on 516 337 individuals (72.7% of all infants born in the period). The prevalence of asthma medication use in young adults born term was 6.33%, compared to 6.91% in those born preterm. Comparing with the term group, we found slightly increased adjusted OR for the use of asthma medication for individuals born at GA 32–36 weeks (n=20 848) OR=1.12 (95% CI=1.06–1.18) and GA 28–31 weeks (n=2 256) OR=1.23 (95% CI=1.05–1.44). In the extremely preterm group (GA=24–27 weeks, n=355) the association was not significant: OR=1.04 (95% CI=0.68–1.58). Conclusion: There was an association between gestational age and the use of asthma medication at 21–30 years, but it was weak. The adjusted OR increased slightly with decreasing GA except in adults born extremely preterm. Further analyses will be performed to investigate our findings.